2020
DOI: 10.1016/s2589-7500(20)30063-7
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning algorithm to detect chronic kidney disease from retinal photographs in community-based populations

Abstract: Background Screening for chronic kidney disease is a challenge in community and primary care settings, even in high-income countries. We developed an artificial intelligence deep learning algorithm (DLA) to detect chronic kidney disease from retinal images, which could add to existing chronic kidney disease screening strategies. MethodsWe used data from three population-based, multiethnic, cross-sectional studies in Singapore and China. The Singapore Epidemiology of Eye Diseases study (SEED, patients aged ≥40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
138
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 29 publications
3
138
3
Order By: Relevance
“…Some possible explanations for this performance include more profound microvascular damage in patients with worse glucose control and the coexistence of signs of diabetic retinopathy and diabetic nephropathy, which were noted to be significantly associated [ 31 , 32 ]. A deep learning algorithm was recently formulated by a research group at the Singapore National Eye Center (SNEC) [ 33 ]. Their algorithm was used to detect CKD with eGFR <60 mL/min/1.73 m 2 by using both retinal images and risk factors, individually and in combination, in 3 population-based screening databases from Singapore and China [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some possible explanations for this performance include more profound microvascular damage in patients with worse glucose control and the coexistence of signs of diabetic retinopathy and diabetic nephropathy, which were noted to be significantly associated [ 31 , 32 ]. A deep learning algorithm was recently formulated by a research group at the Singapore National Eye Center (SNEC) [ 33 ]. Their algorithm was used to detect CKD with eGFR <60 mL/min/1.73 m 2 by using both retinal images and risk factors, individually and in combination, in 3 population-based screening databases from Singapore and China [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 : Manhattan plot of genome-wide association study for retinal vessel tortuosity corrected for phenotypic variables that showed a statistically significant association, i.e. age, sex, and a subset of principal components of genotypes (PCs: 1,2, 5,6,7,8,16,17,18). Refer to Supplementary Material analysis for correlation with potential confounders.…”
Section: Shared Genetic Architecture With Diseasementioning
confidence: 99%
“…Moreover, CKD awareness is as low as 10% and studies to identify the potential benefits and risks of screening, screening measures, and target groups for screening of asymptomatic individuals, would help inform inconsistent screening guidelines that exist across professional bodies [52]. Advances in retinal fundus imaging technology and integration with machine learning approaches will enable rapid, non-invasive, point-of-care diagnoses, which may enhance screening service provision and improved screening compliance [53]. Retinal cameras are common in primary care settings and high street opticians for diabetic retinopathy screening.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal cameras are common in primary care settings and high street opticians for diabetic retinopathy screening. Recent advances in smartphone technology, combined with the utility of machine learning approaches, highlights the feasibility and potential offered by non-invasive retinal photography as an adjunctive or opportunistic screening tool for CKD in the community [53].…”
Section: Discussionmentioning
confidence: 99%